Clinicopathological alteration of symptoms with serotype among dengue infected pediatric patients. Issue 9 (26th May 2022) - Verma, Priya; Banerjee, Sayan; Baskey, Upasana; Dutta, Supradip; Bakshi, Sagnik; Das, Raina; Samanta, Sandip; Dutta, Shanta; Sadhukhan, Provash C.
Abstract: Dengue fever is a self‐limiting, acute febrile illness caused by an arbovirus. This infection may be asymptomatic or symptomatic with its potential life‐threatening form as DHF/DSS. Severe dengue cases occur typically in children due to overproduction of proinflammatory and anti‐inflammatory cytokines (called cytokines storm) as well as increased microvascular permeability in them. This study aimed to find circulating dengue serotype and their clinicopathological association among pediatric patients admitted to tertiary care hospitals in Kolkata, India. Overall, 210 patients were approached, among them, 170 dengue suspected children admitted to three tertiary care hospitals were included in this study. Dengue samples were screened for the presence of dengue NS1 antigen and IgM antibodies by enzyme‐linked immunosorbent assay. Viral RNA was extracted from NS1 seropositive serum samples and subjected to molecular serotyping by semi‐nested reverse‐transcription polymerase chain reaction. All patients were followed up for clinical manifestations and biochemical parameters associated with dengue. Cocirculation of all four serotypes was observed and DENV2 was the major circulating strain. Physiological classification of associated clinical symptoms was done as per WHO guideline and represented as a percentage variable. A multivariate logistic regression approach was used for making a regression model including dengue‐associated clinical symptoms with dengue positivity or negativity as dependent variables. Thrombocytopenia was observed in 69% of patients and the commonest bleeding manifestation was petechia. Liver function profiles of infected patients were observed during follow‐up and represented using a box plot. A significant change in trends of dengue‐associated clinical manifestations and differential expression of liver functional profile with different phases of transition of dengue fever was observed in this study population.